(untitled) (Mongolian Journal of International Affairs, 2020)
As the conception of security consolidates our prosperity to evolve on this planet that revolutionises our social norms and values from time-to-time, it also encounters threats and challenges that could potentially deliver a massive impact to the world. For instance, such security dilemmas would result in transforming the world order, international relations or even the lives of billions. This is the Novel Coronavirus Pandemic of 2019 (COVID-19) and it has changed the world for an indefinite period. Thus, it has forced us into a new phase, new norms and a new world. This paper will examine how this coronavirus outbreak has political, economic and social impacts on the world order through the lens of international relations.